Hepatitis B virus infection and risk of gallstones: A systematic review and meta-analysis - Karn Wijarnpreecha (2018)
Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved. Background/objectives Gallstone disease and its complications are common, particularly in Western populations. Recent studies have reported a significantly increased risk of gallstones among hepatitis C virus-infected patients. However, the data on patients with hepatitis B virus (HBV) infection are still limited. This meta-analysis was carried out with the aim of summarizing all available evidence. Patients and methods A literature search was performed using MEDLINE and the EMBASE database from inception to May 2016. Studies that reported relative risks, odd ratios, or hazard ratios comparing the risk of gallstones among HBV-infected patients versus patients without HBV infection were included. Pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a random-effect, generic inverse-variance method. Results Nine studies fulfilled our eligibility criteria and were included in the analysis. We found no significant association between HBV infection and the risk of gallstones, with a pooled OR of 1.10 (95% CI, 0.91-1.33). The statistical heterogeneity was moderate, with an I 2 of 69%. Subgroup analysis was carried out. The pooled OR of cross-sectional studies was 1.01 (95% CI, 0.91-1.12; I 2 0%), whereas the pooled OR of case-control studies was 1.53 (95% CI, 0.85-2.74; I 2 80%). Conclusion A significant association between HBV infection and the risk of gallstones was not observed in this study.